Stimuli‐Responsive Dynamic Metaholographic Displays with Designer Liquid Crystal Modulators. Issue 50 (10th November 2020) - Kim, Inki; Ansari, Muhammad Afnan; Mehmood, Muhammad Qasim; Kim, Won‐Sik; Jang, Jaehyuck; Zubair, Muhammad; Kim, Young‐Ki; Rho, Junsuk
Abstract: Flat optics, realized by the artificially created 2D material platform called optical metasurfaces, is currently undergoing a science‐to‐technology transition. However, "real‐time" active operations of such flat optical devices remain yet unresolved. Here, liquid crystals (LCs)‐integrated metaholograms for ultracompact dynamic holographic displays are proposed. The anisotropic nature of the LCs allows facile and repeatable manipulation of the polarization of light. Specifically designed ("designer") LCs and efficient helicity‐encoded metaholograms are combined to realize stimuli‐responsive dynamic displays. The designer LC modulators are used as switches that enable a variety of external stimuli (e.g., electric field, heat, surface pressure) to operate holographic images in real‐time. Such a dynamic metaholographic platform will provide a path to external stimuli‐driven "smart" sensing and display applications such as hologram labels for temperature/pressure/touch monitoring and interactive holographic displays with haptic motion recognition. Abstract : Liquid crystal (LC)‐based metamaterial devices, which can sense targeted stimuli such as electric‐field, temperature and pressure, and report them optically by displaying corresponding holograms, are demonstrated. The demonstrated systems enable a variety of applications like hologram labels that indicate freshness of temperature‐sensitive products during storage or transport and interactive holographic displays with touch sensing or motion recognition.